Analysis of the Impact of Covid 19 on Sales of Micro, Small and Medium Enterprises (MSMEs) (Case Study at the MSME Forum in Manado City) - Helda Ruata; Priscillia Weku (Universitas Sam Ratulangi, 2023)
The Covid 19 pandemic had a major impact on the economic sector due to the many restrictions on community activities, especially for Micro, Small and Medium Enterprises at the MSME Forum in Manado City. This study aims to analyze the impact caused by the Covid 19 pandemic and the survival strategies carried out by MSMEs in the midst of the Covid 19 pandemic on sales of Micro, Small and Medium Enterprises at the MSME Forum in Manado City. The research method uses a qualitative type of case study and is descriptive in nature. The data collection process was carried out by means of interviews, observation and documentation with the management of the Manado City MSME Forum. The results of this study indicate that Covid 19 greatly impacted sales at the Manado City MSME Forum, where this was influenced by Government Regulation No. 21 of 2020 concerning Large-Scale Social Restrictions which caused sales at the Manado City MSME Forum to decline due to reduced customers. The survival strategy of the Manado City MSME Forum management in the form of business development training through social media as a means of promoting products has gone well, this is evidenced by the increase in sales and the condition of MSMEs that are able to survive in the midst of a pandemic crisis. It is hoped that the Manado City MSME Forum will continue to make efforts to maintain business because people are more active online, starting from work and shopping using only social media.Keywords: Impact of Covid 19, Strategy